Madura Language Jargon in the Beach Area of Pamekasan - Ria Kasanova; Muhammad Darrin Zuhri (Penerbit STKIP PGRI Bangkalan, 2018)
Pamekasan beach area is very varieties in forms of language. They used more than one various form. This jargon used to make simple when they speak or interact each other. Thus it is clear that the language is not monolithic, not only in one form, but in various forms. Languages that are still within the scope of the same language system (langue) are called language variants. The phenomenon of language other than can be observed as a phenomenon of system or language structure can be observed as a social phenomenon. As a social phenomenon, the use of language in society is influence for understanding in what they speak or what they purpose. In relation to the above matter in this study the researchers further study it through the title of research